Revitalizing Character Education Through Local Culture using Project-Based History Learning in Lampung - Pariska Husnul Khotimah; Windi Khoirun Nisa; Amelia Apriyani; Mia Asma Rani; Rian Dwi Arrahman (Universitas Muhammadiyah Mataram, 2024)
Abstract: This study explores the integration of Project Based Learning with indigenous Lampung cultural values, namely piil pesenggiri (honor), nemui nyimah (hospitality), and sakai sambayan (cooperation), as a strategic approach to strengthen character education in Indonesian senior high schools. Employing a qualitative literature review and thematic analysis of scholarly publications, policy frameworks, and ethnographic research from 2010 to 2024, the study synthesizes culturally responsive pedagogical practices that foster integrity, empathy, responsibility, and civic mindedness. The findings suggest that embedding local cultural wisdom within project-based learning enhances student engagement, facilitates the internalization of moral values, and promotes the development of twenty first century competencies alongside a strong sense of community belonging. A conceptual framework is proposed that maps Lampung cultural values onto the core phases of project-based learning to provide educators with practical and contextually relevant guidance. The study emphasizes the importance of teacher preparation, collaboration with local communities, and culturally grounded curriculum design. This model contributes to national character education objectives while supporting the preservation and relevance of local cultural traditions within formal educational systems.Abstrak: Penelitian ini mengkaji integrasi Pembelajaran Berbasis Proyek (Project Based Learning) dengan nilai-nilai budaya lokal Lampung, yaitu piil pesenggiri (kehormatan), nemui nyimah (keramahtamahan), dan sakai sambayan (gotong royong), sebagai pendekatan strategis untuk memperkuat pendidikan karakter di sekolah menengah atas di Indonesia. Dengan menggunakan kajian literatur kualitatif dan analisis tematik terhadap publikasi ilmiah, kerangka kebijakan, dan penelitian etnografis dari tahun 2010 hingga 2024, studi ini mensintesis praktik pedagogis yang responsif secara budaya yang mendorong integritas, empati, tanggung jawab, dan kesadaran berwarga negara. Temuan menunjukkan bahwa mengintegrasikan kearifan budaya lokal dalam pembelajaran berbasis proyek meningkatkan keterlibatan siswa, memfasilitasi internalisasi nilai-nilai moral, dan mendorong pengembangan kompetensi abad ke-21 bersamaan dengan penguatan rasa kebersamaan dalam komunitas. Sebuah kerangka konseptual diusulkan untuk memetakan nilai-nilai budaya Lampung ke dalam tahapan inti pembelajaran berbasis proyek guna memberikan panduan praktis dan kontekstual bagi para pendidik. Studi ini menekankan pentingnya persiapan guru, kolaborasi dengan komunitas lokal, dan perancangan kurikulum yang berakar pada budaya. Model ini berkontribusi pada tujuan pendidikan karakter nasional sekaligus mendukung pelestarian dan relevansi tradisi budaya lokal dalam sistem pendidikan formal.